Evaluation of The Effects of Storytelling Technique on Vocabulary Learning in Foreign Language Teaching According to Students and Teacher's Views - Nazan Şimşir; Engin Karahan; Şengül Saime Anagün (Anı Publishing, 2019)
This study aimed to examine the effects of the storytelling method in English teaching on the vocabulary learning of sixth grade students. The participants of the study are 43 students, 21 in the experimental group and 22 in the control group. In this study qualitative and quantitative research techniques are used together and converging parallel mix pattern is also used. Data collection tools are achievement test, student and teacher diaries, semi-structured interviews and written opinions of students. In the analysis of the data, descriptive statistical methods and content analysis technique are used. The results reveal that both groups succeeded learning but the results of the experimental group are statistically meaningful. It has been determined that the qualitative results of the study increase the quality of the teaching method used, facilitate learning and contribute to the development of vocabulary knowledge. However, they also stated that the students were experiencing difficulties due to not being accustomed to the method and not using the mother tongue in teaching. In the light of these results, it can be suggested that the storytelling method is used more frequently in order to improve the vocabulary of the students.